Microhabitat utilization and species composition of anurans in Agusan Marsh, Agusan del Sur - Navales, Dexie J. (2009)
A reassessment of the anuran species composition and a survey on microhabitat utilization of anuran species employing the visual encounter technique (VET) were done in Agusan Marsh, Agusan del Sur from may 11 to 20, 2008. A total of 10 species from four anuran families, namely, Bufonidae (2), Ranidae (40, Microhylidae (1), and Rhacophoridae (3) were reckoned. Four sepcies, Fejervarya vittigera Wiegmann, Limnonectes leytensis Boettger, Oreophryne of annulata Stejneger and Philautus cf surdus Peters are identifies Philippine endemics while Pelophyryne lighti Taylor and Philautus acutirostris Peters are considered Mindanao endemics. O. cf annulata, F. vittigera, L. lentensis, P. surdus, Bufo marinus Linnacus, and P. lighti were not observed in previous anuran faunal surveys in the area. However, 16 other species documented by previous surveys were not observed. Based on the distance from body of water and substrate, namely, green leaves, brown leaves, branch, leaf litter, fallen log, bare soil and water, 19 microhabitats were identified in Sago forest, 21 in Terminalia forest, and 12 in Agricultural area. Among these microhabitats, the most utilized ones were waterlooged bare soil, green leaves, and leaf litter which are exploited by F. vittigera, Fejervarya cacrivora Gravenhorst, L. leytensis, O. laevis, and B. marinus that are all known commensals of man. These results suggest that the area is disturbed since the available microhabitats support only those which can adapt to less complex habitat. Voucher specimens of L. leytensis from the agricultural area and F. vittigera from Terminalia forest showed deformities in the toes and observed lacked of phalanges, which can be due to chemical runoffs